A phase II study of radioimmunotherapy with intraventricular 131I‐3F8 for medulloblastoma. Issue 1 (22nd September 2017) - Kramer, Kim; Pandit‐Taskar, Neeta; Humm, John L.; Zanzonico, Pat B.; Haque, Sofia; Dunkel, Ira J.; Wolden, Suzanne L.; Donzelli, Maria; Goldman, Debra A.; Lewis, Jason S.; Lyashchenko, Serge K.; Khakoo, Yasmin; et al.
Abstract: Background: High‐risk and recurrent medulloblastoma (MB) is associated with significant mortality. The murine monoclonal antibody 3F8 targets the cell‐surface disialoganglioside GD2 on MB. We tested the efficacy, toxicity, and dosimetry of compartmental radioimmunotherapy (cRIT) with intraventricular 131 I‐labeled 3F8 in patients with MB on a phase II clinical trial. Methods: Patients with histopathologically confirmed high‐risk or recurrent MB were eligible for cRIT. After determining adequate cerebrospinal fluid (CSF) flow, patients received 2 mCi (where Ci is Curie) 124 I‐3F8 or 131 I‐3F8 with nuclear imaging for dosimetry, followed by up to four therapeutic (10 mCi/dose) 131 I‐3F8 injections. Dosimetry estimates were based on serial CSF and blood samplings over 48 hr plus region‐of‐interest analyses on serial imaging scans. Disease evaluation included pre‐ and posttherapy brain/spine magnetic resonance imaging approximately every 3 months for the first year after treatment, and every 6–12 months thereafter. Results: Forty‐three patients received a total of 167 injections; 42 patients were evaluable for outcome. No treatment‐related deaths occurred. Toxicities related to drug administration included acute bradycardia with somnolence, headache, fatigue, and CSF pleocytosis consistent with chemical meningitis and dystonic reaction. Total CSF absorbed dose was 1, 453 cGy (where Gy is Gray; 350.0–2, 784). Median overall survival from first dose of cRIT was 24.9 months (95% confidence interval [CI]:16.3–55.8). Patients treated in radiographic and cytologic remission were at a lower risk of death compared to patients with radiographically measurable disease (hazard ratio: 0.40, 95% CI: 0.18–0.88, P = 0.024). Conclusions: cRIT with 131 I‐3F8 is safe, has favorable dosimetry to CSF, and when added to salvage therapy using conventional modalities, may have clinical utility in maintaining remission in high‐risk or recurrent MB.